The Role Of Artificial Intelligence (Ai) In The Military Sector (Texas Journal of Engineering and Technology, 2025)
This article focuses on artificial intelligence (AI) and its role in the military sector, particularly analyzing its applications and potential uses. Special attention is given to the implementation of AI technologies in engineering fields, especially in military engineering and sapper units. The article also highlights specific opportunities that AI offers to such units and provides relevant information about these applications